Nurses' knowledge and attitudes toward complementary therapies for cancer: A review of the literature - Juliana Christina; Wendy Abigail; Lesley A Cuthbertson (Elsevier, 2016)
Complementary therapies (CTs) are nonconventional supportive therapies, which are used by the patients with cancer. The use of CTs has been known to alleviate symptoms as a result of chemotherapy and to improve quality of life. However, if CTs are inappropriately used, there may be adverse reactions or no effect resulting in poor support of the cancer treatment. Nurses play an important role in supporting patients with cancer who often seek information regarding CTs. Within their scope of practice, it is expected that nurses have sufficient knowledge about the safety and effective use of CTs, and positive attitudes toward supporting patients who wish to use CTs. This review aims to examine existing literature regarding nurses' knowledge and attitudes toward CTs for patients with cancer. English language articles obtained from recognized nursing and midwifery databases such as CINAHL, Google Scholar, Medline, ProQuest Central, and Scopus for the period between 2002 and 2015 were searched. A total of 96 articles were retrieved using the search terms with only 13 eligible articles meeting the inclusion criteria. Three major themes were identified by the thematic analysis of reviewed studies: nurses' knowledge about CTs, nurses' attitudes toward CTs, and sources information about CTs. The majority of studies investigating nurses' knowledge and attitudes toward the use of CTs for oncology was conducted in developed countries. Overall, it was identified that nurses need to improve their knowledge and skills about CTs so that they were more confident to assist patients in integrating conventional treatment and CTs for cancer management.